Prenatal ambient temperature exposure and cord blood and placental mitochondrial DNA content: Insights from the ENVIRONAGE birth cohort study - Eleni Renaers; Congrong Wang; Esmée M. Bijnens; Michelle Plusquin; Tim S. Nawrot; Dries S. Martens (Environment International)
Background: Mitochondrial DNA content (mtDNAc) at birth is a sensitive biomarker to environmental exposures that may play an important role in later life health. We investigated sensitive time windows for the association between prenatal ambient temperature exposure and newborn mtDNAc. Methods: In the ENVIRONAGE birth cohort (Belgium), we measured cord blood and placental mtDNAc in 911 participants using a quantitative real-time polymerase chain reaction. We associated newborn mtDNAc with average weekly mean temperature during pregnancy using distributed lag nonlinear models (DLNMs). Double-threshold DLNMs were used to study the relationships between ambient temperature and mtDNAc below predefined low (5th, 10th, 15th percentile of the temperature distribution) and above predefined high temperature thresholds (95th, 90th, 85th percentile of the temperature distribution). Findings: Prenatal temperature exposure above the used high temperature thresholds was linked to lower cord blood mtDNAc, with the strongest effect in trimester 2 (cumulative estimates ranging from −21.4% to −25.6%). Placental mtDNAc showed positive and negative associations for high temperature exposure depending on the applied high temperature threshold. Negative associations were observed during trimester 1 using the 90th and 95th percentile threshold (−26.1% and –33.2% lower mtDNAc respectively), and a positive association in trimester 3 when applying the most stringent 95th percentile threshold (127.0%). Low temperature exposure was associated with higher mtDNAc for both cord blood and placenta. Cord blood mtDNAc showed a positive association in trimester 2 when using the 10th percentile threshold (11.3%), while placental mtDNAc showed positive associations during the whole gestation and for all applied thresholds (estimates ranging from 80.8% − 320.6%). Interpretation: Our study shows that in utero temperature exposure is associated with differences in newborn mtDNAc at birth, with stronger associations observed in the placenta. These findings highlight the impact of prenatal ambient temperature exposure on mtDNAc during pregnancy.